Archaeological and historical materials as a means to explore Finnish crop history - Lempiäinen-Avci Mia; Lundström Maria; Huttunen Sanna; Leino Matti W.; Hagenblad Jenny (Routledge, 2022)
In Northern Europe, barley (Hordeum vulgare L.) has been cultivated for almost 6000 years. Thus far, 150-year-old grains from historical collections have been used to investigate the distribution of barley diversity and how the species has spread across the region. Genetic studies of archaeobotanical material from agrarian sites could potentially clarify earlier migration patterns and cast further light on the origin of barley landraces. In this study, we aimed to evaluate different archaeological and historical materials with respect to DNA content, and to explore connections between Late Iron Age and medieval barley populations and historical samples of barley landraces in north-west Europe. The material analysed consisted of archaeological samples of charred barley grains from four sites in southern Finland, and historical material, with 33 samples obtained from two herbaria and the seed collections of the Swedish museum of cultural history.
The DNA concentrations obtained from charred archaeological barley remains were too low for successful KASP genotyping confirming previously reported difficulties in obtaining aDNA from charred remains. Historical samples from herbaria and seed collection confirmed previously shown strong genetic differentiation between two-row and six-row barley. Six-row barley accessions from northern and southern Finland tended to cluster apart, while no geographical structuring was observed among two-row barley. Genotyping of functional markers revealed that the majority of barley cultivated in Finland in the late nineteenth and early twentieth century was late-flowering under increasing day-length, supporting previous findings from northern European barley.